Freeze-Thaw Splitting Strength Analysis of PAC Based on the Gray-Markov Model - Baoyang Yu; Zongguang Sun; Lin Qi (Advances in Materials Science and Engineering, 2021)
In this study, a freeze-thaw split test was carried out to simulate the frost-heaving behavior of permeable asphalt concrete (PAC). Furthermore, the water stability problems caused by spalling and loosening were studied. Through a comparative analysis of the freeze-thaw split ratio of porosities of 19%, 21%, and 24%, the PAC porosity with excellent water stability was determined to be 19–21%. Scanning electron microscopy (SEM) images of PAC with the three porosity values after repeated freezing and thawing verified that the porosities were greater than 24% and the asphalt film peeling area was the largest, resulting in the rapid decline of the PAC freeze-thaw split ratio. The Gray-Markov model was used to predict the water stability of the mixture with a porosity of 21%. Based on the results, a Gray-Markov method for evaluating the PAC water stability in seasonally frozen areas was introduced.